Journal of Pharmaceutical Policy and Practice - Babar, Zaheer
Journal of Pharmaceutical Policy and Practice (formerly known as Southern Med Review) provides a platform for researchers to disseminate empirical research findings, with the aim that people everywhere have access to the medicines they need and use them rationally. The Journal encompasses all aspects of pharmacy including clinical, social, administrative or economic, and provides a platform to researchers, academics and practitioners from around the world to share new evidence, concerns and perspectives.